Family resilience and chemical dependency: perception of mental health professionals - Sonia Regina Zerbetto; Sueli Aparecida Frari Galera; Bianca Oliveira Ruiz
ABSTRACT Objective: To learn the perception of health professionals from the Psychosocial Attention Center for Alcohol and Other Drugs regarding the resilience attributes that are critical to family members of psychoactive substance dependents. Method: A qualitative descriptive study conducted from February to May 2016, using a focus group technique for data collection. In total, 15 professionals participated in the study: 13 health professionals and two administrative professionals. The statements were recorded and transcribed, and these data were analyzed using the technique of thematic content analysis. Results: Health professionals recognize the family resilience attributes needed for efficient and assertive communication, as well as organizational patterns and facilitating family strengths, factors that contribute to improved family relationship and family functionality. Final considerations: This study contributed to a perspective of clinical intervention with family members that is not limited to the negative aspects of family relationship and life, such as fragility and family dysfunction.